ヒガシ クイーンモードランド ノ キオン・カゼ・タイキ ジュンカン - 菊地, 時夫; キクチ, トキオ; Kikuchi, Tokio (1997)
P(論文) 南極氷床の気候を特徴づけている, 気温と風について衛星と風紋からの推定を行った。さらに, 南極氷床をめぐる大気循環について, 風速ベクトルの日変化や上層風のホドグラフの観測から考察を行い, みずほ基地の高い風向一定性が, カタバ風だけでなく一般場の気圧配転からももたらされていることを示した。T. YASUNARI and S. KODAMA (J. Geophys. Res., 98,13063,1992)が示した30-50日周期の気圧配置の変化によって, 偏西風が強まるときはカタバ風が弱まるが, この周期的変化の原因については不明の点が多い。 Proxy observations of wind and temperature are carried out in East Queen Maud Land. The atmospheric circulation patterns are further studied by in situ observation of the diurnal wind vector variation and the upper air soundings. It was revealed that the high wind directional constancy at Mizuho Station is derived not only from the katabatic wind but also from the general synoptic pressure patterns. The katabatic wind is weakened when the westerly wind intensifies as part of the 30 to 50 day cycle synoptic pattern changes (T. YASUNARI and S. KODAMA, J. Geophys. Res., 98,13063,1992) of which the cause is still to be solved. departmental bulletin paper